The Effect of Tax Socialozation, Tax Knowladge, and Tax Sanction on Individual Taxpayer Compliance KPP Pratama Medan Timur - Telaumbanua, Naomi Deswita; Septony B. Siahaan; Yosephine N. Sembiring; Arthur Simanjuntak (Universitas Methodist Indonesia, 2026)
This study examines tax socialization, tax knowledge, and tax sanctions effects on individual taxpayer compliance at KPP Pratama Medan Timur during 2025. Using multiple linear regression on 104 observations, results show tax socialization significantly positively affects compliance (β = 0.201, p = 0.003), demonstrating effective information dissemination. Tax knowledge demonstrates positive but insignificant influence (β = 0.025, p = 0.655), suggesting knowledge alone proves insufficient without motivational factors. Tax sanctions exhibit the strongest significant positive effects (β = 0.336, p = 0.000), signaling deterrence effectiveness. Simultaneous testing confirms significant collective effects (F = 24.167, p = 0.000), explaining substantial compliance variance (R² = 0.420). Findings suggest integrated approaches balancing educational support, capacity building, and credible enforcement optimize compliance outcomes in taxation contexts.